Intrusion-proof connections to the internet - Neo, Daniel Soo Sim (2008)
This project proposes an intrusion-proof security system. This system not only overcomes the weaknesses of present-day security systems, it also provides an uncompromising means of preventing intrusions. Providing such a secure system would not be useful if popular Internet services cannot function across the system. This thesis will describe how electronic mail and file transfers can still function transparently across the intrusion-proof system.